HUBUNGAN DURASI KERJA, FREKUENSI REPETISI DAN SUDUT BAHU DENGAN KELUHAN NYERI BAHU PADA PKERJA BATIK BAGIAN CANTING DI KAMPOENG BATIK LAWEYAN SURAKARTA - Khansa Fauzia Ramadhiani; Baju Widjasena; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Handmade batik craft workers of Kampoeng Batik Laweyan of Surakarta manually do the canting process with traditional tools. The working posture while doing the process may cause pain in joints, ligaments, and tendons, such as shoulder pain. Long working duration, highly repetitive movements, and shoulder’s posture (measured in angles) are risk factors of shoulder pain complaints. The objective of this study is to analyze the correlation of working duration, repetition frequency, and shoulder’s angle with shoulder pain complaints on canting division of batik craft workers. This study is a explanatory research with cross sectional design. The population of this study are craft workers who uses canting, with subjects as much as 34 persons collected by total sampling method. Instruments used in this study are questionnaires (to collect respondent’s characteristics data), observation (to identify repetition frequency), goniometry (to measure shoulder’s angle with working posture figures), palpasy examination (to objectively measure the shoulder pain with physioteraphy). Statistical analysis conducted using Fisher’s Exact. The result showed that there were 95,5% of the respondents who had shoulder pain complaints. The result showed that working duration (p= 0.016) and shoulder’s angle while extending (p= 0.042) have a correlate with shoulder pain complaints. There were no correlation between repetition frequency (p= 1.000) and shoulder’s angle while crafting batik (p= 1.000) with shoulder pain complaints. It’s recommended for the workers to do body stretches, and for the employers to redesign the work station’s layout.